2014
DOI: 10.1021/cn400221u
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Peptoids Modulate Aggregation of Amyloid-Beta 40

Abstract: Alzheimer's disease (AD) is the most common form of dementia and the sixth leading cause of death in the United States. Plaques composed of aggregated amyloid-beta protein (Aβ) accumulate between the neural cells in the brain and are associated with dementia and cellular death. Many strategies have been investigated to prevent Aβ self-assembly into disease-associated β-sheet amyloid aggregates; however, a promising therapeutic has not yet been identified. In this study, a peptoid-based mimic of the peptide KLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates. 89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates.…”
Section: View Article Onlinementioning
confidence: 99%
“…89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates. 89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates.…”
Section: View Article Onlinementioning
confidence: 99%
“…Numerous variations on this approach have been published, where the sequence is modified or appending domains are attached to improve its efficacy. 2024 In a second approach, peptide libraries are screened for binding to full-length A β . 2528 The library-screening approach requires little or no a priori knowledge of desired sequence or structural features.…”
mentioning
confidence: 99%
“…Aβ oligomeric species were prepared through standard protocols and were detected using immunohistochemistry (IHC) in dot blot analysis. 40 Figure S3). The data revealed that GHK did not prevent the formation of oligomeric species, whereas LPFFD and SrVSrFSr showed ~60% and ~75% inhibition, respectively.…”
Section: Inhibition Of Aβ Oligomeric Aggregatesmentioning
confidence: 99%